Characterization of M8 Wheat Mutant Adaptability to Low Land - Muh. Farid BDR; St Rifdah Gusrianty R; Nurul Hikma; Muh. Fikri Al-Qautzar; Nadilla Aprilia (Universitas Sembilanbelas November Kolaka, 2022)
The wheat requirement in Indonesia is still fulfilled by import, which increases annually. To reduce the import dependence, Indonesia is required to elevate the domestic wheat production appropriate to the Indonesian agroclimatic condition by wheat plant breeding mutation. This study was aimed to characterize several mutant wheat commodities, that are adaptive to lowland condition. The experiment was arranged in a completely randomized block design with 16 observed-wheat genotypes (G). The wheat genotypes used were: 1) (G1) N1 200 2.4.B.6, 2) (G2) N 200 2.3.3, 3) (G3) N 200 2.5.2, (G4) N 350 3.6.2, (G5) N 350 3.7.1, (G6) N 300 3.6.1, (G7) N 350 3.1.3, (G8) N 250 3.7.1, (G9) M 200 1.7.1, (G10) S 300 7.9.1, (G11) S 300 2.1, (G12) D 200, and several comparative varieties, such as (G13) Guri-3, (G14) Selayar, (G15) Nias, and (G16) Dewata. The results obtained that the lowland-adapted M8 wheat mutant with high productivity level was found in N 200 2.4.B.6 (2.75 t.ha-1), N 200 2.3.3 (2.69 t.ha-1), and D 350 3.6.2 (2.35 t.ha-1). Characters with the highest heritability level were number of tillers, number of productive tillers, seed weight per panicle, and production. Meanwhile, characters, that were correlated with production, were plant height, number of tillers, number of productive tillers, harvesting age, seed-filling period, number of spikelets per panicle, percentage of empty florets, number of seeds per panicle, and seed weight per panicle